El proceso de formación docente: consideraciones para su desarrollo - Peralta Lino, María (2011)
The teachertraining process which is reviewed and valued in its nature and projection demands interest and engagementtothe institutions in orderto achieve an intellectual high position considering the aspiration which representsthe interventionquality.Having achieved this position, it will be possible to design a better approach and a n ore adequate process far the new knowledge society requirements and the farecasted scenary far a long, medium and short term future.The contents mention and describethree stages in thetraining as well as its correspondent complementsince a centered approach in the development of abilities.